Characterization and shelf-life assessment of hanging rice (Puso). - Pintor, Justine Mariz R.
Food safety and food waste are significant problems the food industry faces, especially staple foods. To minimize these problems, a deeper understanding and knowledge about the product must be acquired. In the study, a staple in Cebu called hanging rice, locally known as puso was studied. The study's main objective were to assess the shelf-life of puso and its physico-chemical properties at ambient temperature for 4 days. The study specifically aimed to characterize the proximate composition of hanging rice, and to conduct a physicochemical analyses, microbial analyses, and sensory evaluation for four days. The analyses used in the study were proximate analysis (moisture content, fat, protein, carbohydrate, crude fiber, and ash), physicochemical analyses (moisture content, water activity, pH, and texture profile ), microbial analyses (TPC, YMC, and B, cereus count), and sensory evaluation (aroma and texture). The results of proximate analysis revealed that puso is composed mainly of water and carbohydrate, containing 46.02 ± 3.60 % and 43.32 ± 3.38 %, respectively. During storage, the moisture content and microbial load of puso increased affecting the texture and pH. With the increase of microbial load, the moisture increased resulting to loss of hardness, and the decrease of pH. In addition, the aroma indicated spoilage during the 3rd day and water activity remain constant. Findings from physicochemical analyses, microbial analyses, and sensory evaluation provided a better understanding of the hanging rice's quality and can be used to determine its optimal shelf life. It revealed that the shelf-life of hanging rice is two (2) days. However, there is a significant risk in consuming puso on its 2nd day of storage due to B. cereus count greater than the safety limit (> 106 cell/g).